Pemantapan Kemampuan Berbicara Bahasa Jepang Bagi Peserta Magang LPK Indonesia Nippon Anugerah Berbasis Aplikasi Praktek Percakapan Bahasa Jepang - yani, Damai; Rahmayanti, Elsa; Sari, Dwi Mutia (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Japanese language skills are a mandatory requirement for Indonesian interns who will work in Japan. Based on interviews with the leadership of LPK INNA (Indonesia Nippon Anugerah) Padang, it is known that the average intern who goes to Japan has Japanese language skills at N4 level or at least N5. At this level, students can read hiragana, katakana and basic kanji, they are can listen and take in information that is spoken slowly. However, interns are still hampered in communicating spontaneously, they are not fluent and stammer in carrying out conversations. In this PKM, training will be given to strengthen Japanese speaking skills to interns at LPK INNA through the Japanese Conversation Practice application. This training aims to: provide an understanding of Japanese culture related to communication and work ethic, practice carrying out daily Japanese conversations, introduce the use of the Japanese Conversation application as a medium for independent practice. The transmission of science and technology uses the SAVI method